Microdrop Human Immunodeficiency Virus Sequencing for Incidence and Drug Resistance Surveillance. (31st January 2021) - Park, Sung Yong; Faraci, Gina; Murphy, Gary; Pilcher, Christopher; Busch, Michael P; Lee, Ha Youn
Abstract: Background: Precise and cost-efficient human immunodeficiency virus (HIV) incidence and drug resistance surveillances are in high demand for the advancement of the 90-90-90 "treatment for all" target. Methods: We developed microdrop HIV sequencing for the HIV incidence and drug resistance assay (HIDA), a single-blood-draw surveillance tool for incidence and drug resistance mutation (DRM) detection. We amplified full-length HIV envelope and pol gene sequences within microdroplets, and this compartmental amplification with long-read high-throughput sequencing enabled us to recover multiple unique sequences. Results: We achieved greater precision in determining the stage of infection than current incidence assays, with a 1.2% false recency rate (proportion of misclassified chronic infections) and a 262-day mean duration of recent infection (average time span of recent infection classification) from 83 recently infected and 81 chronically infected individuals. Microdrop HIV sequencing demonstrated an increased capacity to detect minority variants and linked DRMs. By screening all 93 World Health Organization surveillance DRMs, we detected 6 pretreatment drug resistance mutations with 2.6%–13.2% prevalence and cross-linked mutations. Conclusions: HIDA with microdrop HIV sequencing may promote global HIV real-time surveillance by serving as a precise and high-throughput cross-sectional survey tool that can be generalized for surveillance of other pathogens. Abstract : By amplifying full-length human immunodeficiency virus (HIV) envelope and pol gene sequences within microdroplets, we developed the HIV Incidence and Drug Resistance assay, a single-blood-draw surveillance tool for incidence and drug resistance mutation detection.